Saving behavior among TM staff Kota Bharu / Siti Syarmimi Mohd Isa - Mohd Isa, Siti Syarmimi (2011)
This paper reports an exploratory study on relationship Saving Behaviour among TM staff Kota Bharu with return, income, financial knowledge and family size. The objective of the study is to determine the relationship between return, income, financial knowledge and family size with saving behavior among TM staff Kota Bharu. For this study, the primary data are used and the researcher had distributed the questionnaire among 100 employees in TM Kota Bharu. The data collected was tested by using regressions analysis. This indicates that most of the respondents agreed that there is relationship between the return, income, financial knowledge and family size with saving behavior among TM staff in Kota Bharu. Overall, the researcher concluded that all the variables model is acceptable and reliable for forecasting